Papilloedema and hepatic dysfunction apparently induced by perhexiline maleate (Pexid). Issue 4 (April 1980) - Atkinson, A B; McAreavey, D; Trope, G
Abstract : A patient developed papilloedema and hepatic dysfunction while being treated with perhexiline maleate. These later regressed when the drug was withdrawn. Patients should be monitored for these potentially serious side-effects while on this drug.